A Comparative Study of Energy Efficiency in Tumbling Mills with the Use of Relo Grinding Media - Nikolay Kolev (Metals, 2021)
An evaluation of Relo grinding media (RGM, Reuleaux tetrahedron-shaped bodies) performance versus standard grinding media (balls) was made through a series of grinding tests, including a slight modification of the standard Bond test procedure. Standard Bond tests showed a reduction in the Bond ball mill work index (wi) of the mineral sample used in this study when using Relo grinding media. The modified Bond test procedure is based on using the standard Bond ball work index test but changing the circulating loads (350%, 250%, 150%, 100%). The comparative tests with RGM were carried out at the same number of revolutions as the grinding tests with balls at respective circulating load. The RGM charge yielded a 14% higher net undersize product than balls, which hints at improving energy efficiency and the potential for significant mining industry benefits.